(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Supiandi MI, Ege B, Julung H, Zubaidah S, Mahanal S. 2021. Ethnobotany of traditional medicine in Dayak Jangkang Tribe, Sanggau District, West Kalimantan, Indonesia. Biodiversitas 22: 5417-5424. The Dayak Jangkang tribe has local knowledge about the use of medicinal plants that have been going on for a long time. Unfortunately, the local knowledge of the Dayak Jangkang tribe is currently threatened to disappear because it is delivered orally; there are no written documents and a wasteful lifestyle. The study aimed to document traditional medicinal plants that are utilized by the Dayak Jangkang tribe. The research approach used was qualitative descriptive using the field survey. The study interviewed three informants categories, i.e., the main informant (one customary chairman), key informant (one village head), and recommended informant (eight people who were knowledgeable about medicinal plants). The data were obtained through in-depth interviews and participatory observations. Data analysis used qualitative descriptive. The study got 40 plants that are used for traditional medicine with Zingiberaceae as the most used family. The parts of plants used by the Dayak Jangkang tribe for treatments were roots, bulbs, rhizomes, stems, bark, banana hump, fruit, fruit skins, leaves, fruit, and seeds. The mode of preparation is still considered simple.